Goethe Yearbook 19. - Purdy, Daniel (Goethe Yearbook., 2012)
"The 'Goethe Yearbook' is a publication of the Goethe Society of North America, encouraging North American Goethe scholarship by publishing original English-language contributions to the understanding of Goethe and other authors of the 'Goethezeit' while also welcoming contributions from scholars around the world. Volume 19 of the 'Goethe Yearbook' continues to investigate the connection between Goethe's scientific theories and his aesthetics, with essays on his optics and his plant morphology. A special section examines the central role that Goethe philology has had in establishing practices that shaped the history of 'Germanistik' as a whole. The yearbook also includes essays on legal history and the novella, Goethe 'Lieder', esoteric mysticism in 'Wilhelm Meisters Lehrjahre', and Werther's sexual pathology. The volume also includes three essays re-examining Goethe's aesthetics in the context of the history of deconstruction, as well as the customary book review section. Contributors: Beate Allert, Frauke Berndt, Sean Franzel, Stefan Hajduk, Bernd Hamacher, Jeffrey L. High, Francien Markx, Lavinia Meier-Ewert, Ansgar Mohnkern, Rüdiger Nutt-Kofoth, Edward T. Potter, Chenxi Tang, Robert Walter. Daniel Purdy is Associate Professor of German at Pennsylvania State University. Book review editor Catriona MacLeod is Associate Professor of German at the University of Pennsylvania."--JSTOR website (viewed April 07, 2017).